Getting that thing out of the box: the contribution of self-regulation in innovation processes in human children (Homo sapiens) and a non-human primate species (Sapajus spp.) - Bechtel-Kühne, Sabrina; Voigt, Babett; Pauen, Sabina; Visalberghi, Elisabetta; Sabbatini, Gloria (Journal of Self-Regulation and Regulation, 2017)
The capacity to innovate is regarded as one major cause for explaining the rise of the human species. But how does innovation develop in human ontogeny? Which basic skills are needed to act innovatively? And how do we differ from other species? In our project, we use an interdisciplinary comparative approach and pursue three aims. First, we investigate innovative tool use in preschool children taking a process perspective that allows for a more detailed analysis of why young children may fail. Second, we study potential relations between the process of tool innovation and self-regulation, because self-regulation allows for flexible adaptation to different situations and might be crucial when it comes to solving a problem innovatively. Third, we compare preschool children’s performance to the behavior of capuchin monkeys in an analogue paradigm. The present report describes our project in more detail and outlines the current project state as well as the next steps.
Gesehen am 12.09.2017
Keywords: Innovation; preschoolers; non-human primates; self-regulation
Keywords: Primaten; Werkzeuggebrauch; Lernen; Selbstregulation; Kind; Pädagogische Psychologie; Vorschulkind